Loss of complement regulatory proteins on red blood cells in mild malarial anaemia and in Plasmodium falciparum induced blood-stage infection - Damian A. Oyong; Jessica R. Loughland; Arya SheelaNair; Dean Andrew; Fabian D. L. Rivera; Kim A. Piera; Timothy William; Matthew J. Grigg; Bridget E. Barber; Ashraful Haque; Christian R. Engwerda; James S. McCarthy; et al. (Malaria Journal, 2019)
Abstract Background Anaemia is a major consequence of malaria, caused by the removal of both infected and uninfected red blood cells (RBCs) from the circulation. Complement activation and reduced expression of complement regulatory proteins (CRPs) on RBCs are an important pathogenic mechanism in severe malarial anaemia in both Plasmodium falciparum and Plasmodium vivax infection. However, little is known about loss of CRPs on RBCs during mild malarial anaemia and in low-density infection. Methods The expression of CRP CR1, CD55, CD59, and the phagocytic regulator CD47, on uninfected normocytes and reticulocytes were assessed in individuals from two study populations: (1) P. falciparum and P. vivax-infected patients from a low transmission setting in Sabah, Malaysia; and, (2) malaria-naïve volunteers undergoing P. falciparum induced blood-stage malaria (IBSM). For clinical infections, individuals were categorized into anaemia severity categories based on haemoglobin levels. For IBSM, associations between CRPs and haemoglobin level were investigated. Results CRP expression on RBC was lower in Malaysian individuals with P. falciparum and P. vivax mild malarial anaemia compared to healthy controls. CRP expression was also reduced on RBCs from volunteers during IBSM. Reduction occurred on normocytes and reticulocytes. However, there was no significant association between reduced CRPs and haemoglobin during IBSM. Conclusions Removal of CRPs occurs on both RBCs and reticulocytes during Plasmodium infection even in mild malarial anaemia and at low levels of parasitaemia.